Cytoplasmic polyamines as permeant blockers and modulators of the voltage-gated sodium channel. - Huang, C J (2001)
We report that voltage-gated Na+ channels (Na(V)) from rat muscle (mu1) expressed in HEK293 cells exhibit anomalous rectification of whole-cell outward current under conditions of symmetrical Na+. This behavior gradually fades with time after membrane break-in, as if a diffusible blocking substance in the cytoplasm is slowly diluted by the pipette solution. The degree of such block and rectification is markedly altered by various mutations of the conserved Lys(III) residue in Domain III of the Na(V) channel selectivity filter (DEKA locus), a principal determinant of inorganic ion selectivity and organic cation permeation. Using whole-cell and macropatch recording techniques, we show that two ubiquitous polyamines, spermine and spermidine, are potent voltage-dependent cytoplasmic blockers of mu1 Na(V) current that exhibit relief of block at high positive voltage, a phenomenon that is also enhanced by certain mutations of the Lys(III) residue. In addition, we find that polyamines alter the apparent rate of macroscopic inactivation and exhibit a use-dependent blocking phenomenon reminiscent of the action of local anesthetics. In the presence of a physiological Na+/K+ gradient, spermine also inhibits inward Na(V) current and shifts the voltage dependence of activation and inactivation. Similarities between the endogenous blocking phenomenon observed in whole cells and polyamine block characterized in excised patches suggest that polyamines or related metabolites may function as endogenous modulators of Na(V) channel activity.